(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2017)
Our Journal team is pleased to present its long-anticipated special issue on the scholarship of community engagement with Indigenous communities. Indigenous engagement has been identified by the Journal’s Advisory Board as a priority focus for our Journal and its special issues. Perhaps this emphasis is not surprising for those based in Canada, as Canadians have been witnessing and living through important societal transformations that recently have been gaining momentum in Canada.